Uncovering Bupi Yishen Formula Pharmacological Mechanisms Against Chronic Kidney Disease by Network Pharmacology and Experimental Validation - Zhang, Difei; Liu, Bingran; Jie, Xina; Deng, Jiankun; Lu, Zhaoyu; Lu, Fuhua; Liu, Xusheng (Frontiers in Pharmacology, 2021)
Chronic kidney disease (CKD) is a leading public health problem with high morbidity and mortality, but the therapies remain limited. Bupi Yishen Formula (BYF) - a patent traditional Chinese medicine (TCM) formula - has been proved to be effective for CKD treatment in a high-quality clinical trial. However, BYF's underlying mechanism is unclear. Thus, we aimed to reveal BYF pharmacological mechanism against CKD by network pharmacology and experimental studies. Network pharmacology-based analysis of the drug-compound-target interaction was used to predict the potential pharmacological mechanism and biological basis of BYF. We performed a comprehensive study by detecting the expression levels of fibrotic and inflammatory markers and main molecules of candidate signal pathway in adenine-induced CKD rats and TGF-β1-induced HK-2 cells with the treatment of BYF by western blotting and RT-qPCR analyses. Using small interfering RNA, we assessed the effect of BYF on the TLR4-mediated NF-κB mechanism for CKD renal fibrosis and inflammation. Network pharmacology analysis results identified 369 common targets from BYF and CKD. Based on these common targets, the BYF intervention pathway was analyzed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis. We found that Toll-like receptor (TLR) and NF-κB signaling pathways were enriched. Then, we demonstrated that BYF significantly improved the adenine-induced CKD rat model condition by kidney dysfunction improvement and reversing renal fibrosis and inflammation. Subsequently, we investigated BYF’s effect on the TLR4/NF-κB signaling pathway. We found that TLR4 and phospho-NF-κB (p-p65 and p-IKβα) expression was significantly upregulated in adenine-induced CKD rats, then partially downregulated by BYF. Furthermore, BYF inhibited fibrotic and inflammatory responses, as well as TLR4, p-p65, and p-IKβα in TGF-β1-induced HK-2 cells. Additionally, the BYF inhibitory effect on fibrosis and inflammation, and NF-κB pathway activation were significantly reduced in TGF-β1-induced HK-2 cells transfected with TLR4 siRNA. Altogether, these findings demonstrated that the suppression of TLR4-mediated NF-κB signaling was an important anti-fibrotic and anti-inflammatory mechanism for BYF against CKD. It also provided a molecular basis for new CKD treatment drug candidates.